Implementasi Pemanfaatan Teknologi Meringankan Beban Administratif di UPT SD Negeri 13 Binamu - S, Ramlah; Achruh, A.; R, Rosdiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze 1. How the implementation of technology lightens the administrative burden of teachers at UPT SDN 13 Binamu. 2. What are the challenges and strategies for utilizing technology in lightening the administrative burden of teachers at UPT SDN 13 Binamu. In the context of technological disruption and globalization, teachers are required to integrate technology not only in learning, but also in increasingly complex administrative management. Using a qualitative approach with in-depth interviews and direct observation of teachers at UPT SDN 13 Binamu, this study found that applications such as e-reports and digital communication platforms (WhatsApp) significantly reduced the time and effort in recording attendance, managing student data, and communicating with parents. Teachers reported increased time efficiency, data accuracy, and ease of access to information, allowing them to shift their focus to core pedagogical tasks. However, the study identified the gap in technology adaptation among senior teachers as a major obstacle, leading to the delegation of technology-based administrative tasks to younger teachers. In addition, constraints on personnel administration applications and unstable internet connections are still significant challenges. Therefore, this study recommends targeted and sustainable technology training, as well as the provision of more reliable digital infrastructure to ensure equitable and maximum utilization of technology in supporting administrative efficiency and teacher professionalism at UPT SDN 13 Binamu.